Ugkat - Suico, Alyssa Mariel Umali 1993-; De Guzman, Anne Marie G.; University of the Philippines. College of Mass Communication (2014)
"Ugkat ("unearth") is about unearthing the identity that we've buried in the efforts to level ourselves with cultures that are not our own. In the struggle to move forward, we've been misled into situations causing us to be pitted against one another, and ultimately we end up losing our land, our way of life, and our identity. Yet our rich and beautiful culture is still inside of us is just waiting to be heard. If only we could realize that acknowledging and learning from our roots could contribute greatly to attain true liberation and proper development as a nation."
Vita.
Thesis (A.B. Film)--University of the Philippines Diliman
Keywords: Cultural assimilation; Indigenous peoples; Musicals -- Scores